Efforts to Improve History Learning Outcomes by Using Creative and Productive Learning Models - Priatmoko, Sandika; Alabi, Jimoh Adeniyi; Hong, Sung Ku (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The aim of this research is to determine students' history learning outcomes by applying creative and productive learning models. Methodology: This research is classroom action research carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, reflection. The research subjects were class X high school students. The data collection tools or instruments used in this classroom action research are written test or evaluation instruments to reveal student learning outcomes and observation sheets regarding understanding of student activities and teacher performance. Data analysis is carried out statistically by calculating the average value obtained then the second stage calculate learning completeness. Main Findings: The learning outcomes obtained by students in cycle I showed an improvement compared to before they were given learning using creative and productive models. In cycle II, student learning outcomes showed a better improvement compared to cycle I. Student learning outcomes in cycle II were as follows: the percentage of completion level in cycle II was 84.61%, while students who did not complete the percentage were 15.38. %. So the overall class average is 7.82. The conclusion of this research is that by using the Creative and Productive Learning model there is an increase in learning outcomes on the subject of the origins and distribution of humans in the Indonesian Archipelago. Novelty/Originality of this study: The novelty of this research is that it is useful in the field of education, especially in history subjects as an effort to improve the completeness of student learning outcomes.